2021
DOI: 10.1038/s41598-021-91239-7
|View full text |Cite
|
Sign up to set email alerts
|

Flexible, high mobility short-channel organic thin film transistors and logic circuits based on 4H–21DNTT

Abstract: The low mobility and large contact resistance in organic thin-film transistors (OTFTs) are the two major limiting factors in the development of high-performance organic logic circuits. Here, solution-processed high-performance OTFTs and circuits are reported with a polymeric gate dielectric and 6,6 bis (trans-4-butylcyclohexyl)-dinaphtho[2,1-b:2,1-f]thieno[3,2-b]thiophene (4H–21DNTT) for the organic semiconducting layer. By optimizing and controlling the fabrication conditions, a high saturation mobility of 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 67 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…8−10 The flexible alkyl chains generate liquid crystallinity as well as contributing to the high solubility, which is key for fabricating a uniform polycrystalline film without cracks. 16 Iino and co-workers reported that an asymmetric BTBT derivative 2-phenyl-7-decyl [1]benzothieno- [3,2-b] [1]benzothiophene [Ph-BTBT-C 10 (Figure 1a)] forms a molecularly flat surface with very few grain boundaries in a polycrystalline film, when a liquid crystalline film is cooled to its crystallization temperature. 8 The resulting film is subsequently heat-treated to exhibit a high OFET mobility of >10 cm 2 V −1 s −1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8−10 The flexible alkyl chains generate liquid crystallinity as well as contributing to the high solubility, which is key for fabricating a uniform polycrystalline film without cracks. 16 Iino and co-workers reported that an asymmetric BTBT derivative 2-phenyl-7-decyl [1]benzothieno- [3,2-b] [1]benzothiophene [Ph-BTBT-C 10 (Figure 1a)] forms a molecularly flat surface with very few grain boundaries in a polycrystalline film, when a liquid crystalline film is cooled to its crystallization temperature. 8 The resulting film is subsequently heat-treated to exhibit a high OFET mobility of >10 cm 2 V −1 s −1 .…”
mentioning
confidence: 99%
“…This improvement in solubility is particularly important for organic semiconductors, because conjugated molecules with no alkyl chain are often insoluble in most solvents. Many of the recently developed materials for organic field-effect transistors (OFETs), in fact, accompany alkyl side chains on the conjugated backbone, and they are readily deposited on a solid substrate using solution processes such as spin coating, dip coating, bar coating, blade coating, and inkjet printing techniques, as well as the conventional physical vapor deposition technique.…”
mentioning
confidence: 99%
“…24 These high charge carrier mobilities and exceptional stabilities have opened up more pathways for implementing organic semiconductors in the fabrication of high performance semiconductor devices including organic thin film transistors, [25][26][27][28] organic gas sensors, [29][30][31][32][33] organic optoelectronic devices, [34][35][36][37][38][39][40] and complimentary circuits. [41][42][43] Nevertheless, a challenging issue in organic semiconductor growth is the control of crystallization and morphology. This is mainly caused by the intrinsic crystal misorientation when the organic semiconductor is grown in solution, as reported in many small molecular organic semiconductors.…”
Section: Background and Challengesmentioning
confidence: 99%
“…62 Bilgaiyan et al reported the solution shearing of a 6,6 bis( trans -4-butylcyclohexyl)-dinaphtho[2,1- b :2,1- f ]thieno[3,2- b ]thiophene (4H-21DNTT) organic semiconductor based thin film transistor and obtained a mobility of 10.5 cm 2 V −1 s −1 . 63 The 4H-21DNTT based CMOS inverter circuit showed sharp switching behaviors with a 31.5 signal gain. Second, substrate patterning based methods involve the tuning of substrate wettability by using surfactant treatment and/or photolithography patterning, which can effectively confine the deposition of organic semiconductor solutions as well as the subsequent crystal growth and alignment.…”
Section: Introductionmentioning
confidence: 98%